Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species - Marinone, María Cristina; Urcola, Juan Ignacio; Rabet, Nicolas (Zootaxa, 2016)
A new spinicaudatan species, Eulimnadia pampa sp. nov., is described from Argentina mostly based on the differential egg morphology. This species was collected from rainwater pools from Buenos Aires City and the provinces of Buenos Aires and Entre Ríos, and compared to other Neotropical species. Previous Argentine record of E. brasiliensis is shown to belong to our new species, which represents the southernmost Neotropical Eulimnadia. We also present new records of the Paraguayan Eulimnadia ovisimilis Martin and Belk, 1989 from northeastern Argentina. Eulimnadia santiaguensis is treated as a species inquirenda, thus we recognize only three Eulimnadia species in Argentina: E. pampa sp. nov., E. ovilunata and E. ovisimilis, and we provide a brief indentification key. We present the first description and SEM images of the putative Eulimnadia spermatophore, which we found in the new species.